Evidence for Activation of Toll-Like Receptor and Receptor for Advanced Glycation End Products in Preterm Birth - Taketoshi Noguchi; Toshiyuki Sado; Katsuhiko Naruse; Hiroshi Shigetomi; Akira Onogi; Shoji Haruta; Ryuji Kawaguchi; Akira Nagai; Yasuhito Tanase; Shozo Yoshida; Takashi Kitanaka; Hidekazu Oi; et al. (Hindawi Limited, 2010)
Objective. Individuals with inflammation have a myriad of pregnancy aberrations including increasing their preterm birth risk. Toll-like receptors (TLRs) and receptor for advanced glycation end products (RAGE) and their ligands were all found to play a key role in inflammation. In the present study, we reviewed TLR and RAGE expression, their ligands, and signaling in preterm birth. Research Design and Methods. A systematic search was performed in the electronic databases PubMed and ScienceDirect up to July 2010, combining the keywords "preterm birth," "TLR", "RAGE", "danger signal", "alarmin", "genomewide," "microarray," and "proteomics" with specific expression profiles of genes and proteins. Results. This paper provides data on TLR and RAGE levels and critical downstream signaling events including NF-kappaB-dependent proinflammatory cytokine expression in preterm birth. About half of the genes and proteins specifically present in preterm birth have the properties of endogenous ligands "alarmin" for receptor activation. The interactions between the TLR-mediated acute inflammation and RAGE-mediated chronic inflammation have clear implications for preterm birth via the TLR and RAGE system, which may be acting collectively. Conclusions. TLR and RAGE expression and their ligands, signaling, and functional activation are increased in preterm birth and may contribute to the proinflammatory state.